2022
DOI: 10.3390/jcm11247381
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Oxygenated Machine Perfusion (HOPE) Prior to Liver Transplantation Mitigates Post-Reperfusion Syndrome and Perioperative Electrolyte Shifts

Abstract: (1) Background: Post-reperfusion syndrome (PRS) and electrolyte shifts (ES) represent considerable challenges during liver transplantation (LT) being associated with significant morbidity. We aimed to investigate the impact of hypothermic oxygenated machine perfusion (HOPE) on PRS and ES in LT. (2) Methods: In this retrospective study, we compared intraoperative parameters of 100 LTs, with 50 HOPE preconditioned liver grafts and 50 grafts stored in static cold storage (SCS). During reperfusion phase, prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, further studies are required to confirm the effect of HOPE on long-term patient prognosis. Similarly, a retrospective non-PSM study 26 of 100 liver transplant recipients showed that HOPE reduced the incidence of EAD by 44%. Patrono et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, further studies are required to confirm the effect of HOPE on long-term patient prognosis. Similarly, a retrospective non-PSM study 26 of 100 liver transplant recipients showed that HOPE reduced the incidence of EAD by 44%. Patrono et al .…”
Section: Discussionmentioning
confidence: 91%
“…1 ). The four excluded unmatched studies 24 27 (three 24 26 did not use the matching method and one 27 used inverse probability of treatment weighting, but no post-inverse probability of treatment weighting data were available; even after contacting the corresponding author of the study, no data were available, so this study was classified as a unmatched study) are summarized in Supplementary Table S1 (Supplemental Digital Content 4, http://links.lww.com/JS9/B67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, CIT is related to PRS [ 12 ] and IRI which are known risk factors for graft loss [ 13 ]. HOPE has been shown to improve graft preservation by actively oxygenating the graft associated with shorter CIT [ 8 ], translating into decreased PRS [ 10 , 25 , 26 ], decreased EAD, ischemic type biliary complications and graft loss [ 11 ] in adult LT. In our institution, we therefore implemented HOPE for ex-situ split liver grafts since 2020 aiming at improving graft preservation in PSLT.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical observations are supported by experimental data showing a reduction of mitochondrial damage with HOPE which translates into a reduction of the hepatic inflammasome [ 27 , 28 ]. Indeed, HOPE replaces cold ischemia by an active oxygenation of the graft during preservation thus improving mitochondrial function, uploading the ATP cellular pool [ 28 , 29 ] and mitigating IRI [ 10 , 25 , 26 ]. Applying HOPE during ex-situ liver splitting thus combines the benefit of shorter CIT, inherent to this strategy, to mitochondrial metabolism recovery.…”
Section: Discussionmentioning
confidence: 99%
“…MP is expected to increase the pool of transplantable organs. 4,24 Nevertheless, implementing this technology outside the controlled environment of RCT. is full of challenges imposed by clinical practice.…”
Section: Discussionmentioning
confidence: 99%